THE POWER OF INFLUENCE : ANALISIS DAMPAK INFLUENCER MARKETING, DAYA TARIK DAN FREKUENSI POSTING PADA BRAND AWARENESS BUTIK EMY COLLECTION - Ismail Azis, Hijir (MEDIA RISET EKONOMI [MR.EKO], 2025)
The purpose of this study is to explain the extent to which the effectiveness of implementing Influencer Marketing strategies in increasing consumer awareness of the Emy Collection Boutique brand on social media, analyzing the influence of content delivered by influencers on the emergence of potential consumer interest in buying fashion products from Emy Collection Boutique, and identifying the main factors that play a role in the success of cooperation between brands and influencers in encouraging an increase in direct purchases of Emy Collection. By using purposive sampling as a sampling technique at the Amy Collection boutique. The type of research used is Quantitative research. The analytical tools used are Multiple Linear Regression, Classical Assumption Test and t-test (partial) with the SPSS 27.0 for windows program. The results of the analysis obtained that Influencer Marketing, Attraction and Posting Frequency all have an effect on increasing Emy Collection Brand awareness.